Association of vaspin rs2236242 gene polymorphism with serum vaspin level, insulin resistance and diabetes in an Iranian diabetic/ pre-diabetic population - hosseini, maria; nezhadali, masoumeh; hedayati, mehdi (Journal of Medical Biochemistry, 2020)
Abstract Background/aim: In recent years the role of vaspin as an insulin- sensitizer has been studied widely. This is the investigation that studied the association of vaspin polymorphism rs2236242 on vaspin level and the risk of type 2 diabetes and insulin resistant on pre-diabetic/ diabetic population. Material and method: A case-control study is conducted on 160 participants includes eighty participants holding (FBG) fasting blood glucose 70-100 (mg/dl) in normal group and eighty participants holding FBG≥100 (mg/dl) in diabetic/pre-diabetic group. The serum vaspin and insulin was determined with ELISA and biochemical variables by standard method. Tetra arms amplification system for vaspin gene was performed. Statistical analysis was done using SPSS software version 20. Results: The means of age, BMI, WC, HC, FBS and vaspin was significantly different between normal and T2DM/IFG group (P-value<0.05). rs2236242 showed association with Hip circumference (P-value<0.05). A significant association between allele A of rs2236242 with type 2 diabetes was seen (P-value<0.001). The vaspin level showed negative correlation with fasting blood glucose (FBG). Conclusions: Allele A of rs2236242 is a protective risk for type 2 diabetes but no association of rs2236242 with insulin resistant was seen. Lower level of vaspin is a predictor for progression of type 2 diabetes.